Study of interfacial reaction during reflow soldering of Sn-Ag-Cu lead-free solders on bare coppper and immersion silver surface finishes - Abu Hassan, Nurfazlin (2009)
Due to increasing environmental and health concerns related to the toxicity of traditional tin-lead solders, lead-free solders appear as promising replacement for the eutectic solder alloy in flip chip technology. Then a surface finish is designed to protect the copper surface against oxidation as well as provide a diffusion barrier against rapid diffusion between the liquid tin in the solder alloy and copper. In this research, an investigation has been carried out to investigate the effect of multiple reflow and solder bump size during soldering between three types of lead-free solders which are Sn-3.0Ag-0.5Cu, Sn-3.8Ag-0.7Cu and Sn-4.0Ag-0.5Cu on Copper and Immersion Silver (ImAg) surface finishes. Two different solder ball sizes were used; 200 µm and 700µm, and the solder joints were subjected to three reflows at the same temperature. The IMC’s formed were characterized in terms of thickness, morphology and composition. From the research findings, it was observed that solder bump size, which also relates to solder volume, has a significant effect on the formation of intermetallics thickness in the solder joint. The mean thickness of the intermetallics for smaller solder balls was found to be thicker than the bigger solder balls. ImAg produced thinner IMC’s compared to copper surface finish. However, these IMCs grew thicker and changed their morphologies when exposed to multiple reflow, but the compositions were more or less the same. For the Cu surface finish, Cu6Sn5 intermetallic compounds with scallop morphology are formed at the solder/ surface finish interface.